Peran Akademik dalam Pengembangan PAUD: Pendampingan Holistik Integratif oleh Program Studi PIAUD IAIN Lhokseumawe: Pengabdian - Noval Fuadi; Jufri; Mutia Sari (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This mentoring program aims to increase the understanding and capacity of educators and early childhood education personnel in North Aceh Regency in implementing the Integrative Holistic Early Childhood Education model, as a form of implementation of the Tri Dharma of Higher Education. The method used is Participatory Action Research with a problem solving and participatory approach, which is carried out through the stages of problem identification, preparation, socialization, implementation, monitoring, and evaluation. The activity involved 15 Early Childhood Education units as samples. The results of the mentoring showed a significant increase in participants' understanding, from 45% to 85%. The implementation of Integrative Holistic services in the assistance unit was achieved with the following percentages: education services 50%, health, nutrition, and care 25%, parenting 15%, protection 5%, and welfare 5%. Participants assessed that mentoring is very useful for optimizing services for children. It is concluded that academic mentoring based on Participatory Action Research is effective in building the ability to practice Early Childhood Education based on Integrative Holistic in the field.